Participant experiences receiving acupuncture for acute musculoskeletal pain in an emergency department: A qualitative evaluation. - Anna Tupetz; Madison Frazier; Amy O'Regan; Mitchell Knisely; Olivia TumSuden; Erica Walker; Charlotte Sununu; Oliver Glass; Ann Miller-Maxwell; Catherine A Staton; Stephanie A Eucker (PLoS ONE)
Objective Acupuncture is an evidence-based pain treatment in clinic settings, but its optimal delivery has not been established in emergency departments (EDs). As part of an adaptive pragmatic randomized controlled trial of ED acupuncture for acute musculoskeletal pain (NCT04290741), we embedded a qualitative evaluation of acupuncture treatment acceptability and suggestions for improvement from study participants receiving acupuncture in the ED. Methods Semi-structured interviews conducted remotely evaluated factors impacting patients' perspectives, willingness to participate in, and experiences with ED acupuncture. The codebook was iteratively developed, and recruitment and analysis continued until information saturation was reached. Results Twenty-eight participants receiving ED acupuncture between February 2020-March 2021 were interviewed, with median age 44 years, 46.4% female, and 61% having never previously received acupuncture. Overall, ED patients with acute musculoskeletal pain expressed interest in acupuncture and reported an overall positive experience. Most reported acupuncture met their expectations for pain improvement, and many reported additional improvements in stress, anxiety, and sleep quality. Participants with a positive experience were more likely to recommend acupuncture to others. Key positive aspects included open communication with compassionate and knowledgeable acupuncturists. Participants found the ED setting acceptable and convenient for receiving acupuncture. Furthermore, participants provided actionable feedback like addressing fear of needles to improve the ED acupuncture experience. Conclusions In conclusion, ED patients with acute musculoskeletal pain were interested in and had positive experiences with acupuncture treatment for pain and found the ED setting acceptable and convenient. Participant feedback can be used to improve acupuncture treatment in the ED.